The supply of foreign talent: How skill-biased technology drives the skill mix of immigrants. Evidence from Switzerland 1990-2010 - Andreas Beerli; Ronald Indergand; Johannes Kunz (ETH Zurich, KOF Swiss Economic Institute, 2017)
An important goal of immigration policy is facilitating the entry and supply of workers whose skills are scarce in national labour markets. In recent decades, the introduction of information and communication technology [ICT] fuelled the demand for highly skilled workers at the expense of lower skill groups throughout the developed world. In this paper, we show that the skill mix of newly arriving immigrants strongly responded to this shift in the demand for skills. Exploiting the fact that different regions in Switzerland were differentially exposed to ICT due to their pre-ICT industrial composition, we present evidence suggesting more exposed regions experienced stronger growth in relative employment and wage premia for highly skilled workers between 1990 and 2010. We find robust evidence that regions with higher initial ICT exposure experienced a considerably stronger relative in influx of highly skilled immigrants. Taken together, these results strongly suggest that immigrants responded to skill-biased changes in economic opportunities. Complementing these findings, we document whether and how the response of immigrants to skill demand changed when Switzerland abolished immigration restrictions for European workers.
Keywords: F22; J61; J24; J31; J23; 330; immigrant sorting; international migration; routine-biased technical change; information and communication technology; skill supply